Feasibility, safety and outcomes of ambulation within 2 h postoperatively in patients with lung cancer undergoing thoracoscopic surgery. Issue 4 (27th July 2021) - Liu, Tingting; Feng, Jing; Ge, Ling; Jin, Fengxia; Zhou, Chao; Liu, Xiaoxin
Abstract: Aims: The aims of this study were to evaluate the safety, feasibility and outcomes of ambulation within 2 h after thoracoscopic surgery in patients with lung cancer. Background: There are no consensus guidelines on the ideal time for early ambulation following thoracic surgery, although enhanced recovery programmes have been proposed since years. Methods: This non‐randomized, concurrent‐control study was conducted on patients who underwent thoracoscopic surgery between October 2020 and February 2021. Participants were assigned to either the observation group (ambulation within 2 h of extubation) or the control group (ambulation on the first postoperative day). Results: Of the 325 patients who were eligible, 227 were included in the study. Eighty‐three per cent of patients were able to walk any distance within 2 h of extubation, and no adverse events occurred in patients. The length of hospital stay and time to first postoperative flatus were significantly shorter in the observation group than in the control group. There were no differences in the occurrence of postoperative complications and orthostatic hypotension, readmission rate and 6‐min walk distance at discharge. Conclusion: Ambulation within 2 h of extubation was safe and feasible and could lead to better recovery in patients with lung cancer undergoing thoracoscopic surgery. Summary statement: What is already known about this topic? There are few reports of ambulation within 2 h after surgery in patients with lung cancer, whether it is safe and feasible is still challenging due to insufficient evidence. Enhanced recovery after surgery pathways have been shown to effectively shorten the length of hospital stay and decrease postoperative complication rates, but few studies have focused on whether individual elements (e.g., early ambulation) also have the positive effects on these outcomes in patients with lung cancer. What this paper adds? Ambulation within 2 h of extubation was safe and feasible in patients with lung cancer undergoing thoracoscopic surgery. Ambulation within 2 h of extubation could improve recovery and shorten the length of hospital stay and time to first postoperative flatus compared with walking on the first postoperative day. The implications of this paper: This study makes a significant contribution to the literature because it has the potential to inspire policy changes regarding the ideal time for ambulation in patients undergoing thoracoscopic surgery. This study can contribute to raising the compliance of patients for postoperative ambulation and ensuring quality nursing care and patient safety.